Beauveria bassiana (Bals.) Vuill للمرض الفطري Tribolium confusum دراسة قابلية إصابة خنافس الدقيق المتشابهة - طلحة نجاح خليفة; محفوظ نوال عبدالسالم (The Libyan Journal of Science, 2018)
This study reveals the data of 50 soil samples for April and May and 21 soil samples for Septembe - November, 2016 obtained from Tripoli University farm, Sidi Almasry, Ain Zarah, Soug Algomaa and Tajoura to infect the great wax moth larvae Galleriaa mellonella. Results showed that 47 wax moth larvae were infected with Beauveria bassiana. Significant differences at 0.01 levels were obtained for means of 7 and 14 days of fungal infection and no significant differences on adults and larvae of confused flour beetle. No significant differences of fungal infection were observed between wet concentration 1x10³, 1x106, 1x108 conidia / ml on adults and larvae of confused flour beetle. But, significant differences at 0.05 levels were clearly shown between dry and wet fungal concentrations on the insect infection. In comparison, similar results were confirmed for September- November period for the fungus infection to adults and larvae of confused flour beetle, including treatment days of 7 and 14 replications, in presence of suitable temperature and relative humidity. The study recommends the use of B. bassiana as biological control agent in Integrated Pest Management (IPM) for controlling stored insect pests.